Street coder : the rules to break and how to break them - Kapanoğlu, Sedat (Manning Publications Co., 2022)
Street Coder teaches you how to handle the realities of day-to-day coding as a software developer. Self-taught guru Sedat Kapanoğlu shares down-and-dirty advice that's rooted in his personal hands-on experience, not abstract theory or ivory-tower ideology. You'll learn how to adapt what you've learned from books and classes to the challenges you'll face on the job. As you go, you'll get tips on everything from technical implementations to handling a paranoid manager.